STUDY OF NODULATION AND NITROGEN FIXATION IN INTRODUCED CULTIVARS AND CANDIDATE LINES OF PEA (PISUM SATIVUM L.) GROWN AT TWO NITROGENOUS NUTRITION LEVELS - L. V. Omel’yanuk; K. K. Sidorova; V. K. Shumny (Вавиловский журнал генетики и селекции, 2015)
Symbiotic traits – nodulation, nitrogen fixation, and performance – have been studied in seven introduced cultivars and three candidate lines of pea (Pisum sativum L.) The cultivars grown at two nitrogen nutrition levels differ in traits associated with nodulation and nitrogen fixation. The results can be utilized in pea breeding for nitrogen fixation.